2018
DOI: 10.1590/1983-40632018v4853064
|View full text |Cite
|
Sign up to set email alerts
|

Yield characteristics of cherry tomato cultivated with and without shading screen at different irrigation levels

Abstract: The use of shading screen in vegetable crops sensitive to the radiation excess, associated with the effective water use via irrigation, allows for yield gains. This study aimed to evaluate the yield characteristics of cherry tomato cultivated with and without shading screen and different irrigation levels. A randomized block design was used, in a 4 x 2 factorial arrangement, with four irrigation levels (140 %, 160 %, 180 % and 200 % of the reference evapotranspiration - ETo) and two cherry tomato hybrids (Wand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…For the longitudinal and equatorial diameter, the increase was directly proportional to the increase in the volume of water applied. The linear equation models obtained in this study are like those observed by other authors evaluating tomatoes' horticultural responses to different irrigation levels [42][43][44][45][46].…”
Section: Fruit Qualitysupporting
confidence: 82%
“…For the longitudinal and equatorial diameter, the increase was directly proportional to the increase in the volume of water applied. The linear equation models obtained in this study are like those observed by other authors evaluating tomatoes' horticultural responses to different irrigation levels [42][43][44][45][46].…”
Section: Fruit Qualitysupporting
confidence: 82%
“…Being that cultivation in full sun influenced the closure of the stomata and sweating interruption. Santiago et al (2018), observed microclimatic and productive differences of cherry tomato under protected conditions in the region of Juazeiro-BA; associating the low productivity of the plants conducted in full sun to the high atmospheric demand. Which is characterized mainly by high incidence of solar radiation and low air humidity, since a high rate of evaporation, consequently reducing available water content and nutrients absorption.…”
Section: Results and Discusionmentioning
confidence: 91%
“…Tomato (Solanum lycopersicum L.) is one of the main vegetables produced in the world and among the different groups, cherry (S. lycopersicum var. cerasiforme) has the main characteristics of good productivity and higher concentration of soluble solids when compared to other groups (PÉK et al, 2014;SANTIAGO et al, 2018). Recent studies have shown the effect of B on cherry tomatoes, such as increased shelf life and vitamin C content (ISLAM et al, 2016;ISLAM et al, 2018).…”
Section: Introductionmentioning
confidence: 99%